Ekonomi Dan Bisnis Pengaruh Digital Marketing, Kualitas Produk, Dan Store Atmosphere Terhadap Keputusan Pembelian McDonald’s Di Surabaya (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas 17 Agustus 1945 Surabaya: Pemasaran - Widodo, Bryan Nafiri; Budiarti, Endah (Research Journal of Social Science and Economics, 2025)
With digital technology advancing at a rapid pace. Technology is becoming a tool that helps in fulfilling most human needs. These developments have had a significant impact on the marketing industry. Therefore, entrepreneurs must identify suitable promotional strategies for their companies with the aim of using technological advancements to increase purchasing decisions. For example, this can be done by means of Digital Marketing, Product Quality and Store Atmosphere.This study was conducted to determine and analyze whether Digital Marketing, Product Quality and Store Atmosphere have a positive and significant effect on McDonald’s Purchasing Decisions both simultaneously and partially. The sample in this study were students of the Faculty of Economics and Business, University of August 17, 1945 Surabaya. The sample of this study amounted to 100 respondents. The technique used in this research is the Non-Probability Sampling Technique which is a non-randomly selected sampling technique using the Quota Sampling type with the Lemeshow formula. Data collection through distributing questionnaires online, namely through G-Form. The data analysis method uses multiple regression analysis with SPSS version 26 software for data processing.Through this research, it can be known and analyzed that Digital Marketing has a Positive and Significant Effect on McDonald’s Purchasing Decisions. Research can also be known and analyzed that Product Quality has a Positive and Significant Effect on McDonald’s Purchasing Decisions. In addition, research can also be known and analyzed that Store Atmosphere has a Positive and Significant Effect on McDonald’s Purchasing Decisions.” “Kewords : Digital Marketing, Product Quality, Store Atmosphere, Purchase Decision